Effects of sleep deprivation on the mental health of adolescents: a systematic review - Kavya Johri; Rea Pillai; Ansh Kulkarni; Rajesh Balkrishnan (Sleep Science and Practice)
Abstract This paper seeks to identify the factors and impact of sleep deprivation in the adolescent population and suggests pertinent preventive measures. We used diagnostic indicators and keywords to examine literature published from 2013 through bibliographic search tools. The risk of mental health problems is increasing, alongside cognitive and social impairments. Risk factors associated with sleep deprivation include circadian rhythm shifts, early school start times, and lifestyle choices. This may be catalyzed by additional factors such as excessive homework and utilization of social media, which contribute to inadequate duration and quality of sleep, leading to decreased academic and social challenges, higher risk-taking behaviors, stress, suicidal ideation, and diminished physical health. Delaying school start times, limiting electronic device usage before bed, promoting physical activity, and implementing sleep hygiene education can help improve sleep quality and overall well-being in adolescents by acting as preventative measures for this population. Parental involvement, through awareness and the implementation of consistent bedtimes, is also crucial for supporting healthy sleep habits. More research is needed to develop effective interventions within education and healthcare that can address the growing sleep and mental health crisis.